An examination of three key factors: Alcohol, trauma and child welfare: Fetal Alcohol Spectrum Disorder and the Northwest Territories of Canada: Brightening Our Home Fires - Badry, Dorothy; Wight Felske, Aileen (First Peoples Child & Family Review, 2013)
This article was generated from the research project “Brightening Our Home Fires” (BOHF), a Photovoice project on woman’s health and wellness that took place in the Northwest Territories (NT) from 2010-2012. This research was funded by the First Nations and Inuit Health Branch (FNIHB) of Canada. Approximately 30 women from four different communities in the NT participated in this project; Behchokö, Ulukhaktok, Yellowknife and Lutsel 'ke. The method utilized in this study was Photovoice, a Participatory Action Research (PAR) model that is identified as a qualitative research approach. While the research project was a Fetal Alcohol Spectrum Disorder (FASD) prevention project, the broader focus was on issues related to health and healing within a northern context in the NT from the perspective of northern women, and within the construct of health. The primary focus of this article is the presentation of a model that was generated from a review of the research literature gaining a deeper understanding of broader social concerns in the NT. Three key factors are highlighted as critical in developing a deeper understanding of the context of women’s health issues that are important to consider in FASD prevention work: 1) trauma, 2) alcohol abuse and 3) child welfare involvement and the impact on communities in the northern territories of Canada as it presently exists in the NT. This research served to provide a broad perspective of social problems that may be mitigating factors in the presentation of FASD in a northern context.